Pengalaman Ibu dalam Mendampingi Kondisi Menarche pada Remaja Putri Penyandang Cerebral Palsy - Anastasya Ecclesya Ambarura; Andri Kenti Gayatina; Apolonilda Antonilda Ina (Dinasti Research, 2024)
Children with Cerebral Palsy are very dependent on the help of other people, especially parents who play a role in meeting their needs. One of the obligations and responsibilities of parents towards their children is to provide attention and guidance in matters of reproduction and sexuality, one of which is accompanying the first menstruation or menarche. Data from the Center for Disease Control and Prevention (CDC) through population studies shows that the global prevalence of CP in children ranges from 2 to 4 incidents of CP out of 1,000 live births. The aim of this research is to determine mothers' experiences in assisting menarche conditions in adolescent girls with Cerebral Palsy. The research uses qualitative methods with a descriptive phenomenological approach. Data were collected using semi-structured interviews. The research was conducted on 4 participants at the Foundation for the Development of Disabled Children (YPAC with research time 14-27 July 2024. The results of the interviews were transcribed and analyzed using the Colaizzi method. The results of the analysis drew similarities and made them into themes. The characteristics of this research were mothers aged 36-47 years who have experience accompanying menarche children with Cerebral Palsy. There are 3 themes of results, namely feelings of confusion, overwhelm, worry in accompanying children at menarche, how mothers deal with children's moods during menstruation, and mothers getting assistance from other people when children menstruate. Themes that appear in participants, namely feelings of confusion, overwhelm, worry, how to deal with the child's mood and help from other people when accompanying a CP child with menarche. Psychological support and giving the child space to express his feelings are the mother's way of dealing with the child's condition